Investigation of traceability and recall plans of food manufacturing plants and small and medium enterprises (SMEs) in Pasir Mas, Kelantan - Afiza Izzati Mat Aris (2014)
The flourishing of food industry needs an excellent and reliable traceability system to ensure that consumers are persistently well protected from unconsciously consuming unsafe food which is harmful to their health. The traceability systems are being implemented by different food industries all around the world including Malaysia. However, in perspective to the Malaysian food industry, there are only a few industries and Small Medium Enterprises (SMEs) that are aware of the system. This study aims to determine the implementation of traceability system by identifying the flow of food products either backward or forward through the supply chain. This traceability system also identified the Critical Traceability Points (CTPs) that influenced the tracing of the unsafe product supply. Extensive literature review regarding traceability system was done to understand of the system implementation. In this study, survey was conducted based on the traceability system and questionnaires which consist of three sections were used as survey data which were analyzed by using SPSS 16.0. It involved 17 participants of manufacturing plants and 53 participants of SMEs from the area of Pasir Mas. Kelantan. The study findings show that manufacturers of plants and SMEs are interested in implementing traceability system but lack information and advanced technologies. Only 52.9% of the participants had implemented or were interested in implementation of traceability system. According to the survey, several factors of success traceability implementation are reduced due to time limitations, does not provide benefit to the company's economy, no policy guidance and support from government and also extensive traceability regulations, laws and standards. The outcome of this study determined that 37 of manufacturing plants and SMEs implemented the traceability system and 33 of the manufacturing plants and SMEs did not implement the traceability system.